1997
DOI: 10.1097/00000374-199711000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Course of Alcohol Withdrawal in Women and Men

Abstract: A retrospective study compared the course of alcohol withdrawal, including delirium tremens, in women and men hospitalized in the Nowowiejski Hospital in Warsaw from 1973 to 1987. Medical records pertaining to 1179 patients were analyzed; 13.8% of these patients were women and 86.2% were men. The study showed that women began intensive alcohol drinking later than men (p < 0.0001), but the period between the onset of alcohol abuse and the first occurrence of alcohol withdrawal was shorter in women than in men (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In agreement, an animal study reported that female mice showed more severe cell death in the forebrain compared to male mice [8]. On the other hand, more men than women displayed withdrawal syndromes such as seizure, tremor, anxiety, and insomnia [7, 9]. The greater vulnerability of male than female subjects has been shown in an animal study where EW-induced anxiety was more severe in male rats than female rats [10].…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…In agreement, an animal study reported that female mice showed more severe cell death in the forebrain compared to male mice [8]. On the other hand, more men than women displayed withdrawal syndromes such as seizure, tremor, anxiety, and insomnia [7, 9]. The greater vulnerability of male than female subjects has been shown in an animal study where EW-induced anxiety was more severe in male rats than female rats [10].…”
Section: Introductionmentioning
confidence: 55%
“…Sex differences in EW have been shown in human and animals studies which yielded somewhat controversial results. The period between the onset of alcohol abuse and the first occurrence of EW syndromes was shorter in women than men [7], indicating that women are more vulnerable to EW. In agreement, an animal study reported that female mice showed more severe cell death in the forebrain compared to male mice [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not clear if sex differences may exist with regard to the manifestation of severe alcohol withdrawal or the “kindling-like” phenomenon observed with repeated alcohol withdrawals. While animal studies suggest a greater susceptibility to withdrawal seizure and greater duration of withdrawal in male rodents as compared to female rats or mice [6,150], studies of human samples suggest that either few sex differences exist [61,84] or that males display alcohol withdrawal of a greater severity than females [139,155]. Further, a link between withdrawal seizure and overt neurodegeneration has not been established.…”
Section: The Role Of Withdrawal In Alcohol Dependencementioning
confidence: 99%